Exertional compartment syndrome in an equestrian - Lisle, D. K.; Tucker, J. B. (The Physician and Sportsmedicine, 2004)
When evaluating lower-leg pain, the clinician must consider compartment syndrome resulting from exercise, even in the absence of trauma or if the exercise is seemingly benign. Equestrian sports would seem an unlikely source of acute compartment syndrome, but the examiner should consider unusual mechanisms of injury in any case. Although intracompartment tissue pressure measurements can help make the diagnosis, excessive pain is a more reliable early warning sign of acute compartment syndrome. A timely diagnosis and immediate surgical treatment may prevent serious long-term sequelae.